PERANAN MODAL SOSIAL DALAM PELAKSANAAN KELEMBAGAAN HUTAN LINDUNG ADAT - Micho, Andri (Jurnal Ilmu Administrasi Negara, 2016)
The Role of Social Capital in Implementing Institutional Indigenous Protected Forest. This study aims to describe the role of social capital in the implementation of traditional institutions and the Kampar Kenegerian to describe and analyze the form of forest management applied by indigenous peoples Kenegerian Kampar so that it can work effectively in defending the existence and preservation of Indigenous Protected Forest Kenegerian Kampar. The method used descriptive qualitative served basis. The informants are indigenous prince, community leaders, village heads and other informants that are relevant to this study. Data was collected through interviews, observation and documentation study. Data were analyzed using an interactive model, starting from data reduction, data presentation and conclusion. The results showed that the prohibition of Indigenous Forest Sustainability Kampar Kenegerian can survive because of the social capital (social capital) confidence (trust) and values (Value) in traditional institutions that are owned by Indigenous Peoples.